Improving energy flexibility of a net-zero energy house using a solar-assisted air conditioning system with thermal energy storage and demand-side management. (1st March 2021) - Ren, Haoshan; Sun, Yongjun; Albdoor, Ahmed K.; Tyagi, V.V.; Pandey, A.K.; Ma, Zhenjun
Highlights: Energy flexibility of a net-zero energy house with a solar HVAC system is studied. Using solar energy, thermal energy storage and demand-side management is studied. Improvement of energy flexibility was achieved solely by demand-side management. Thermal energy storage and demand-side management facilitated further improvement. Abstract: The increasing penetration of solar energy into buildings can mitigate the great challenges of energy shortage and global warming, while the inherent intermittence of solar energy could endanger power grids. This study investigated the energy flexibility of a net-zero energy (NZE) house using a solar-assisted air conditioning system with integrated thermal energy storage (TES) and demand-side management (DSM) strategies. The main contribution is to investigate and reveal the interactions among the utilisation of solar energy, thermal energy storage, and DSM strategies, to improve building energy flexibility. A simulation system of the NZE house was first developed using TRNSYS. A total of 40 alternative designs of the solar-assisted air conditioning system with TES were formulated by exhausting the combination of the photovoltaic/thermal (PV/T) collectors and a phase change material TES unit, and four DSM strategies including over-heating/cooling, pre-heating/cooling, temperature set-point relaxation, and heat pump charging TES. The results showed that heat pump solar contribution (i.e. the ratio of the energy consumption provided by PV to its total energy consumption) of 0.79 was achieved by using DSM strategies. Using TES unit could further increase solar contribution to nearly 1.0. The influence of the temperature set-point relaxation and over-heating/cooling strategies on energy flexibility was negligible when the over-heating/cooling and/or heat pump charging TES were used. The 1% peak grid import was mostly contributed by the appliances when the designs with high energy flexibility were used. The findings of this study could be used to facilitate the development of NZE buildings with increased energy flexibility.